2001
DOI: 10.1034/j.1600-0765.2001.360506.x
|View full text |Cite
|
Sign up to set email alerts
|

Levels of tissue inhibitor of metalloproteinases‐1 and matrix metalloproteinases‐1 and ‐8 in gingival crevicular fluid following treatment with enamel matrix derivative (EMDOGAIN®)

Abstract: The mechanism of enamel matrix derivative (EM D) action on the periodontal wound healing process is not well understood. However, earlier in vitro studies from our laboratory demonstrated that EMD stimulated the proliferation of both periodontal ligament and gingival fibroblast cells. Therefore, the purpose of this study was to further evaluate the effect of EMD on the early wound healing process by assessing the protein levels of matrix metalloproteinases (MMPs) and tissue inhibitors of metalloproteinases (TI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
1
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 22 publications
4
51
1
1
Order By: Relevance
“…In those cases, other assays might be more suitable, such as enzyme-linked immunosorbent assay (ELISA) or Western blot analysis. For example, MMP-8 is difficult to detect with zymography, but with other techniques it might be possible to measure protein levels (78,79). …”
Section: Problemsmentioning
confidence: 99%
“…In those cases, other assays might be more suitable, such as enzyme-linked immunosorbent assay (ELISA) or Western blot analysis. For example, MMP-8 is difficult to detect with zymography, but with other techniques it might be possible to measure protein levels (78,79). …”
Section: Problemsmentioning
confidence: 99%
“…This anecdotal observation was recently substantiated by the statistically significant reduction of matrix metalloproteinase levels observed in EMD-treated defects during the postsurgical inflammatory healing phase. 91 In addition, it was reported that higher proportions of EMD sites reached several clinical signs characterizing resolution of gingival inflammation faster during wound healing. 92 In conclusion, local irritation tests, sensitization studies, and observations of clinical reactions indicated that EMD is a well tolerated and clinically safe product to use in periodontal therapy.…”
Section: Safety and Adverse Reactionsmentioning
confidence: 99%
“…2,[11][12][13][14][15][16] A time resolved immunofluorometric assay (IFMA), ELISA 그리고 a dentoAnalyzer device 등을 이용해서 MMP-8을 분석해 본 결과 방법에 상관없이 일치하는 결과 를 보였다는 연구도 있었지만, 16 ELISA의 경우 다른 방법 들과는 다른 종류의 antibody를 사용하게 되어서 조금 다 른 결과를 보일 수도 있다고 보고되기도 했다. 17 치주영역에 서는 치은 열구액을 채취하여 chair-side에서 MMP-8의 농도를 측정하여 진단에 이용할 수 있는 기구가 개발되어 있다.…”
Section: 또한 같은 샘플을 희석하여 Mmp-8과 Sp의 분석에 동시에 사용할 수 있는 이점이 있었다unclassified